1987
DOI: 10.1093/carcin/8.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in the metabolism of N-nitroso(2-hydroxypropyl)(2-oxopropyl)amine

Abstract: Hamsters and rats metabolize [1-14C]N-nitroso(2-hydroxypropyl)(2-oxopropyl)amine (HPOP) and N-nitrosobis(2-oxopropyl)amine (BOP) to yield N-nitrosobis(2-hydroxypropyl)-amine (BHP), glucuronic acid conjugates of HPOP and BHP, the sulfate ester of HPOP and 14C-labeled urea, all of which are excreted, and 14CO2 which is both incorporated in the urea cycle, and exhaled. The extent of metabolism and the ratios of these metabolites does not vary significantly with age or sex of the animal, however, marked species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Boettcher et al [37], when comparing rats and humans, found that in rats, the sulfate conjugation of antipyrine was the predominant pathway, whereas in humans, antipyrine glucuronides were most prominent, with the sulfate formation being dose-dependent. Kokkinakis et al [38], for example, found that N -nitroso(2-hydroxy-propyl)(2-oxopropyl) amine in hamsters is conjugated with sulfuric acid ten times faster than in rats, where the glucuronic acid conjugates are predominant. Wong [39] found that sulfate conjugation of 4-hydroxy-3-methoxyphe-nylethanol is predominant in most animal species such as mouse, cat, rat, rabbit, and guinea-pig, whereas in humans, only the glucuronide was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Boettcher et al [37], when comparing rats and humans, found that in rats, the sulfate conjugation of antipyrine was the predominant pathway, whereas in humans, antipyrine glucuronides were most prominent, with the sulfate formation being dose-dependent. Kokkinakis et al [38], for example, found that N -nitroso(2-hydroxy-propyl)(2-oxopropyl) amine in hamsters is conjugated with sulfuric acid ten times faster than in rats, where the glucuronic acid conjugates are predominant. Wong [39] found that sulfate conjugation of 4-hydroxy-3-methoxyphe-nylethanol is predominant in most animal species such as mouse, cat, rat, rabbit, and guinea-pig, whereas in humans, only the glucuronide was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in quantitative and/or qualitative metabolic degradation, route of administration, variations in strain-related enzymatic activation and other intrinsic factors might be involved in determining target organ specificity and susceptibility. 32) In line with the low incidence of preneoplastic lesions, no tumors were found in the selected organs of male or female 0.1% DHPN-treated Wistar rats. Hasegawa et al 20) and Yoshida et al 27) respectively reported incidences of 100% and 20% of neoplasias in the lung and of 5% and 7% in the thyroid gland in F344 male rats exposed to 0.1% DHPN.…”
Section: Discussionmentioning
confidence: 82%
“…Although glucuronic acid conjugation is generally considered to be a detoxifying metabolic pathway, it has been suggested that it may play a role in the activation of nitrosamine carcinogens (31). The formation of glucuronides of hydroxylated nitrosamines has also been reported by Wiessler and Rossnagel (32), Suzuki and Okada (33), and Kokkinakis and co-workers (34,35).…”
Section: Discussionmentioning
confidence: 82%